Mak Di Juk Siang Tradition in Lampung indigenous community: A Perspective on Islamic Marriage Law in Building Family Resilience - Wahyu Abdul Jafar; Badrun Taman; Ahmed Hameed Kareem; Muntaser Ahmad Alqudah; Nashat Mohammad Abdel Qader Bani Hamad; Iim Fahimah (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2026)
This study explores the practice of Mak Di Juk Siang among the Lampung indigenous community as a mechanism for promoting family resilience, with particular attention to gender perspectives and the application of living fiqh munākahāt. Mak Di Juk Siang is a customary practice that governs divorce proceedings while reinforcing moral responsibility and honor in marital relationships. The research employs a qualitative approach through ethnographic fieldwork, including in-depth interviews with married couples, customary leaders, and relevant authorities, participatory observation of traditional activities, and analysis of related customary documThis study explores the practice of Mak Di Juk Siang in the Lampung indigenous community as a way of promoting family resilience, with particular attention to gender perspectives and the application of living fiqh munākahāt. Mak Di Juk Siang is a customary practice that governs divorce proceedings while reinforcing moral responsibility and honour in marital relationships. The research employs a qualitative approach through ethnographic fieldwork, including in-depth interviews with married couples, customary leaders, and relevant authorities, participatory observation of traditional activities, and analysis of related customary documents. The findings reveal that Mak Di Juk Siang functions as a form of social control over divorce and as a means of fostering gender awareness within the household. The practice highlights the roles of both women and men in maintaining marital harmony and emphasises the balance between each spouse's rights and responsibilities. It also demonstrates the synergy between local Piil Pesenggiri values and the principles of fiqh munākahāt in establishing harmonious family relationships. From an academic perspective, this study helps further understand the interaction between Islamic law, customary practices, and gender dynamics, while illustrating the relevance of living fiqh as an adaptive, culturally established approach. The findings may also inform the development of family law policies that are sensitive to local customs and promote gender justice in Indonesia. Keywords: family resilience; Mak Di Juk siang; marriage law.